O processo decisório estratégico de estabelecimento de parcerias para aprendizagem interorganizacional na indústria farmacêutica do Estado de São Paulo - Corbacho, Valmir (2009)
This thesis attempts to study and to examine the new ways of relationship based on interorganizational models in the pharmaceutical industry in the State of São Paulo. This segment is a privileged object of study for this purpose due to its needs of high investments in research and development, the dynamic nature of its environment, the complexity and the way it disseminates the knowledge, as well as its no accumulative technology. These features and idiosyncrasies of the pharmaceutical segment allow a wider collaborative relationship, mainly in order to develop new products. The possibility of creating collaborative nets amplifies the vision strictly rational and competitive of these companies. This work supports that these organizational abilities do not belong anymore to these firms. The nets and the arrangements are part of the organizations, but they go too far the boundaries. Therefore, it emerges a new approach for the theory of the organizations. It means an approximation that understands how the new configuration of the organizational environment is. The aim of this work is to verify how the decision s process occurs in the organizations that developed strategic partnerships in the pharmaceutical industry. Thus, it analyses three firms located in the State of São Paulo. To answer this question, the essay selected the cases in which the technology and the dynamic environmental are examples of high complexity. Due to this reason, we applied the methodology of multiple cases. We selected three national firms that established collaborative partnership to the research, development, commercialization and medicaments distribution under the patent of international companies. The final objective is to investigate the circumstances that involve the company s decision when it decides to enter in partnership with other, the intrinsic risks and the benefits, such as the release of an innovative medicine, the technological improvements and the conquest of a new niche of market. We conclude that the decisory process to establish the collaborative partnership is marked by the use of practices that minimize the limited rationality due to the high investments needed to the research and development, besides that it is a high risk to the companies to succeed in this partnership. Another point that must be highlighted: the collaborative partnership, due to the creation of resources to investments in research and development, was supported by interorganizational networks that have the objective of maintaining the market position while innovative efforts were engendered to introduce new medicaments in the sector.